Core promoters of the penicillin biosynthesis genes and quantitative RT-PCR analysis of these genes in high and low production strain of Penicillium chrysogenum - Šmidák, Roman; Jopčík, Martin; Královičová, Martina; Gajdošíková, Jana; Kormanec, Ján; Timko, Jozef; Turňa, Ján (Folia microbiologica, 2010)
The transcription start points of the penicillin biosynthesis genes from Penicillium chrysogenum were mapped using the primer extension method. For each of the three genes consensus sequences of the core promoter elements were identified, supporting the notion that the basal transcription of these genes is mediated separately. Interestingly, transcription start of the pcbC gene is located within the potential Inr element with no TATA box-like sequence being found at expected position. This is in contrast to pcbAB and penDE genes with proposed TATA boxes or even to Aspergillus nidulans ipnA (pcbC) gene indicating possible differences in basal transcription regulation. Using the quantitative RT-PCR analysis the expression of all three biosynthesis genes was monitored in both the high and low production strain of P. chrysogenum during a 3-d cultivation under production conditions. The differences were found between the strains in time regulation and transcript levels of the biosynthesis genes. Furthermore, we showed that the effect of higher gene dosage on productivity in the production strain is amplified by more efficient transcription of the biosynthesis genes with the RNA levels approximately 37- and 12-times higher, respectively, than in a low production strain.
Keywords: financování organizované; Base Sequence; Penicillium chrysogenum; Fungal Proteins; sekvence aminokyselin; Molecular Sequence Data; polymerázová řetězová reakce s reverzní transkripcí; Amino Acid Sequence; Financing, Organized; molekulární sekvence - údaje; Reverse Transcriptase Polymerase Chain Reaction; fungální proteiny; peniciliny; Penicillins; sekvence nukleotidů; Gene Expression Regulation, Fungal; regulace genové exprese u hub; promotorové oblasti (genetika); Promoter Regions, Genetic